Agenda-setting in first sessions of business coaching—a focus on coaches’ practices to manage the agenda and establish the working alliance - Jautz, Sabine; Graf, Eva-Maria; Fleischhacker, Melanie; Dionne, Frédérick (Frontiers in Psychology, 2023)
Agenda-setting is a central communicative task for professionals and a joint activity of all participants particularly at the onset of helping interactions such as coaching. Agreeing on goal(s) and assigning tasks alongside establishing a trustful bond prepare the ground for the success of the interaction. The professional agent initiates and sets the agenda as part of their professional role and responsibility, i.e., based on their professional epistemic and deontic authority. Concurrently, by orienting to clients' epistemic authority and by yielding power, control, and agency to clients to co-manage the ensuing interaction, agenda-setting is the first opportunity for client-centeredness, which is a central characteristic and success factor for the working alliance in coaching. We take first steps in filling a research gap by providing a first analysis of the interactional unfolding of agenda-setting in coaching and by showcasing that and how agenda-setting as a joint activity of coach and client contributes to their working alliance. More precisely, we investigate agenda-management practices in five first sessions of business coaching to (1) document and analyze how the joint activity 'agenda-setting' is implemented via various (coach-initiated) social actions, (2) detail their contribution to establishing the working alliance, and (3) to interpret the emerging practices of agenda-management against the concept of 'client-centeredness'. For the analysis, we draw on conceptual and methodological resources from interactional linguistics alongside linguistic pragmatics and conversation analysis. We found 117 instances of 'agenda-setting' in our data which can be assigned to the six seven social actions